PROFITABILITAS DAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN HIGH DAN LOW PROFILE - Apriyanti, Ni Made Windya; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
This study aimed to examine the effect of profitability is proxied by the return on assets on corporate social responsibility company of high and low profile. Samples were selected using purposive sampling method and acquired 68 companies categorized high profile and low profile of 129 companies categorized. Testing the hypothesis in this study was done by using simple linear regression analysis and Mann - Whitney test. This study was the first to obtain results, there is a difference between the profitability of the company high profile and low profile. Secondly, there is a difference in the company's CSR disclosure of high-profile and low profile. Third, proxy profitability with return on assets has positive effect on the company's CSR high and low profile.
Keywords: profitability, return on assets, corporate social responsibility, high-profile, low profile